2003
DOI: 10.1097/01.mp.0000042420.21088.c7
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of Histologic Features of Steatohepatitis with Other Forms of Chronic Liver Disease

Abstract: Steatohepatitis, of either alcoholic or nonalcoholic etiologies, is ultimately diagnosed by clinicalpathologic correlation and is characterized histologically by lesions that differ from the portal-based chronic inflammation and fibrosis of most other forms of chronic liver disease. With the increasing prevalence of steatohepatitis in our society, it is likely that some patients will have coexistent clinical and/or histopathologic findings of steatohepatitis concurrently with another form of liver disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
18

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(120 citation statements)
references
References 51 publications
3
99
0
18
Order By: Relevance
“…Because of the high prevalence of risk factors for NAFLD and NASH, it is not uncommon for patients with other chronic liver diseases to exhibit coexisting histological features of NAFLD ( 168 ). Coexistent hepatic steatosis is common in chronic hepatitis C (HCV) infection and is strongly associated with more advanced liver disease ( 169 -171 ).…”
Section: Nafld In Patients With Other Chronic Liver Diseasesmentioning
confidence: 99%
“…Because of the high prevalence of risk factors for NAFLD and NASH, it is not uncommon for patients with other chronic liver diseases to exhibit coexisting histological features of NAFLD ( 168 ). Coexistent hepatic steatosis is common in chronic hepatitis C (HCV) infection and is strongly associated with more advanced liver disease ( 169 -171 ).…”
Section: Nafld In Patients With Other Chronic Liver Diseasesmentioning
confidence: 99%
“…Because of the high prevalence of risk factors for NAFLD and NASH, it is not uncommon for patients with other chronic liver diseases to exhibit co-existing histological features of NAFLD. 168 Coexistent hepatic steatosis is common in chronic hepatitis C (HCV) infection and is strongly associated with more advanced liver disease. [169][170][171] Another large study showed high prevalence of steatosis (40.5%) and steatohepatitis (15%) in patients with primary biliary cirrhosis (PBC), 172 although at least some of the steatosis and steatohepatitis in that study was suspected to be due to alcohol consumption.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…In fact, the presence of co-existent nonalcoholic steatohepatitis, the more aggressive form of NAFLD, is found in 5%-10% of biopsy specimens from patients with CHC. 12,13 The etiology of hepatic steatosis in patients with NAFLD appears to be centered on both peripheral and hepatic insulin resistance. Increased energy stores occurring in obese individuals lead to enhanced lipolysis and generation of free fatty acids.…”
Section: Steatosis Mediated Via Host Metabolic Factorsmentioning
confidence: 99%